2014
DOI: 10.1144/sp412.1
|View full text |Cite
|
Sign up to set email alerts
|

Eocene partial melting recorded in peritectic garnets from kyanite-gneiss, Greater Himalayan Sequence, central Nepal

Abstract: Anatectic melt inclusions (nanogranites and nanotonalites) have been found in garnet\ud of kyanite-gneiss at the bottom of the Greater Himalayan Sequence (GHS) along the Kali\ud Gandaki valley, central Nepal, c. 1 km structurally above the Main Central Thrust (MCT). In\ud situ U–Th–Pb dating of monazite included in garnets, in the same structural positions as melt\ud inclusions, allowed us to constrain partial melting starting at c. 41–36 Ma. Eocene partial\ud melting occurred during prograde metamorphism in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 101 publications
(140 reference statements)
6
64
0
Order By: Relevance
“…Plagioclase around quartz inclusions in kyanite was sporadically observed (e.g. Carosi et al, 2014a). This feature suggests that also kyanite was present during melting (Carosi et al, 2014a).…”
Section: Outcrop Description and Sample Petrographymentioning
confidence: 94%
See 3 more Smart Citations
“…Plagioclase around quartz inclusions in kyanite was sporadically observed (e.g. Carosi et al, 2014a). This feature suggests that also kyanite was present during melting (Carosi et al, 2014a).…”
Section: Outcrop Description and Sample Petrographymentioning
confidence: 94%
“…Based on Ar-Ar geochronology, Vannay and Hodges (1996) suggested that the whole GHS rapidly cooled below the white-mica closure temperature (300-430°C) during the Early-Middle Miocene (13-15 Ma). Carosi et al (2014a) identified "nanogranites" as inclusions in garnets from kyanite-bearing rocks (bottom of the upper GHS) testifying that these rocks have experienced melting starting at c. 41-36 Ma, based on U-Pb in situ monazite ages.…”
Section: The Ghs In the Kali Gandaki Valleymentioning
confidence: 99%
See 2 more Smart Citations
“…U -Th -Pb dating of monazite in kyanitebearing gneiss from the central Nepal Himalaya by Carosi et al (2014) indicates that a tonalite melt was entrapped within the gneiss at 41-36 Ma in the kyanite stability field. They found that the Oligocene age melts are not limited to the South Tibetan Gneiss Domes, but also occur in the frontal part of the Himalayan belt, as well as in the Namche Barwa syntaxis.…”
mentioning
confidence: 99%